Rifampicin-Liposomes for Mycobacterium abscessus Infection Treatment: Intracellular Uptake and Antibacterial Activity Evaluation - Federica Rinaldi; Patrizia Nadia Hanieh; Simona Sennato; Federica De Santis; Jacopo Forte; Maurizio Fraziano; Stefano Casciardi; Carlotta Marianecci; Federico Bordi; Maria Carafa (MDPI AG, 2021)
Treatment of pulmonary infections caused by Mycobacterium abscessus are extremely difficult to treat, as this species is naturally resistant to many common antibiotics. Liposomes are vesicular nanocarriers suitable for hydrophilic and lipophilic drug loading, able to deliver drugs to the target site, and successfully used in different pharmaceutical applications. Moreover, liposomes are biocompatible, biodegradable and nontoxic vesicles and nebulized liposomes are efficient in targeting antibacterial agents to macrophages. The present aim was to formulate rifampicin-loaded liposomes (RIF-Lipo) for lung delivery, in order to increase the local concentration of the antibiotic. Unilamellar liposomal vesicles composed of anionic DPPG mixed with HSPC for rifampicin delivery were designed, prepared, and characterized. Samples were prepared by using the thin-film hydration method. RIF-Lipo and unloaded liposomes were characterized in terms of size, ζ-potential, bilayer features, stability and in different biological media. Rifampicin's entrapment efficiency and release were also evaluated. Finally, biological activity of RIF-loaded liposomes in Mycobacterium abscessus-infected macrophages was investigated. The results show that RIF-lipo induce a significantly better reduction of intracellular Mycobacterium abscessus viability than the treatment with free drug. Liposome formulation of rifampicin may represent a valuable strategy to enhance the biological activity of the drug against intracellular mycobacteria.